PsycEXTRA Dataset 2006
DOI: 10.1037/e525892015-001
|View full text |Cite
|
Sign up to set email alerts
|

Online Victimization of Youth: Five Years Later

Abstract: Hampshire to conduct this second survey is vital to maintaining the consistency of research methods in order to get the most accurate interpretation of the results. Dr. Finkelhor has been a well-known national authority on child sexual abuse. The conclusions from YISS-1 have formed the basis for many educational initiatives. The work of Dr. Finkelhor and his colleagues represents a valuable addition to our knowledge and awareness of this difficult and complex problem. We thank staff members at NCMEC and the U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(256 citation statements)
references
References 19 publications
9
232
0
15
Order By: Relevance
“…Eligibility criteria were consistent with 2 previous YISSs. 13,14 Table 1 provides details of the sample characteristics.…”
Section: Samplementioning
confidence: 99%
“…Eligibility criteria were consistent with 2 previous YISSs. 13,14 Table 1 provides details of the sample characteristics.…”
Section: Samplementioning
confidence: 99%
“…A national study reports that 13% of youth between the ages of 10 and 17 received an unwanted sexual solicitation or approach over the Internet in the last year (Wolak, Mitchell & Finkelhor, 2006). Four percent of youth received an aggressive sexual solicitation in which a solicitor asked to meet them somewhere, called them on the telephone, sent them regular mail, money or gifts.…”
Section: Internet Sexual Exploitation and Abusementioning
confidence: 99%
“…Therefore the true figure will be far greater than prevalence statistics indicate, but 64% of 2391 reports made to the Child Exploitation and Online Protection Centre (CEOP) in the UK by members of the public, in 2009 and 2010 were related to grooming [9]. In prevalence studies, Ospina, Harstall and Dennet's [10] meta-analysis found most studies report between 13% [11] and 19% [12] of young people aged 10-17 years had received sexual solicitations online. However, in a recent study of adolescent behaviour online, Whittle, Hamilton-Giachritsis, Bishopp and Beech [13] found 33% of 354 thirteen and fourteen year olds reported having been approached sexually online.…”
Section: Introductionmentioning
confidence: 99%